Complete testing coverage for the early infant diagnosis algorithm and associated factors among infants exposed to HIV, Uganda, 2017-2019. - Rebecca Akunzirwe; Julie R Harris; Peter Chris Kawungezi; Mercy W Wanyana; Tom Lutalo; Phoebe Monalisa Namukanja; Augustina Delaney; Richard Migisha; Esther Nyamugisa; Doreen Ondo; Philip Kasibante; Daniel Kadobera; et al. (PLoS ONE)
Background Early infant diagnosis (EID) facilitates early initiation into HIV care for identified HIV-positive infants. According to the Uganda Ministry of Health, EID testing algorithm, testing for infants exposed to HIV (IEH) should occur at <6 weeks, 9 and 18 months of age, and 6 weeks after stopping breastfeeding. Uganda has faced challenges with loss to follow-up (LTFU) of IEH for EID. We assessed complete testing coverage (CTC) to the EID algorithm for IEH and associated factors. Methods We analyzed data from the 'Impact of the National Program for the Prevention of Vertical Transmission (PVT) of HIV in Uganda (2017-2019)' study. Mothers living with HIV whose infants tested HIV-negative at 4-12 weeks were enrolled in a prospective cohort (2017 - 2018) and followed until the IEH tested positive, died, was LTFU, or reached 18 months of age. We computed the proportion of IEH tested according to the EID algorithm among surviving infants. CTC was defined as undergoing HIV tests at three designated time points (excluding the 6 weeks after breastfeeding cessation) if HIV negative. IEH who were diagnosed with HIV but were tested at all recommended tests until that point were also considered to have CTC. We evaluated factors associated with CTC using modified Poisson regression. Results Among 1,804 IEH, 912 (51%) were male. Of the 1,804 IEH at baseline, 27 (1%) died. Among the 1,777 IEH included in the primary outcome analysis, 1,282 (72%) completed the study and 941 (53%) infants had CTC according to the EID testing algorithm including 40 (2%) who tested HIV-positive. Perceived discrimination due to HIV status [RR = 0.77, 95%CI (0.65-0.92)], having fewer pregnancies [RR = 0.97, 95%CI (0.68-0.99)], and reporting sexual violence [RR = 0.82, 95%CI (0.73-0.93)] by the mother of IEH were associated with non-CTC. Conclusion About half of IEH were tested at the recommended time points. Interventions to address stigma and sexual violence for mothers may improve CTC for the EID algorithm. Investigations are needed to explore associations between sexual violence, parity, and CTC for the EID algorithm.